Keterlibatan notaris dalam penegakan hukum kasus korupsi alat-alat kesehatan - Tengku Keizerina Devi Azwar; Ningrum Natasya Sirait (Integritas: Jurnal Antikorupsi, 2025)
Corruption in the procurement of medical equipment remains a major challenge in public health governance. This article explores the role of notaries in such corruption cases, particulary the legalization of falsified documents and invocation of the right to refuse testimony (hak ingkar), which often hinder legal proceedings. Using a qualitative approach and case study analysis, this research examines two notable corruption cases where notaries were summoned as witnesses. The study also assesses the institutional role and effectiveness of the Notary Honorary Council (MKN) in upholding professional ethics. Findings indicate that although notaries are rarely prosecuted as perpetrators, their passive or indirect involvement poses ethical and legal risks. The article recommends reforms to limit the application of hak ingkar in corruption trials, improve oversight, and enhance ethical education. These efforts are critical to prevent notarial functions from being exploited in corrupt procurement practices.